Crescent of crisis : U.S.-European strategy for the greater Middle East - Daalder, Ivo H.; Gnesotto, Nicole; Gordon, Philip H., 1962- (Book collections on Project MUSE., 2006)
The greater Middle East is beset by a crescent of crisisa region of urgent danger stretching from Pakistan to Afghanistan, through Iran and Iraq, all the way to the Syria/Lebanon question and the Israeli-Palestinian conflict. The specific problems range from terrorism and nuclear proliferation to the rise of fundamentalism and a lack of democracy. These crises pose perhaps the most pressing security challenges to Europe and the United States today. Unfortunately, the U.S. and its allies across the Atlantic generally have approached them in separate ways, often resulting in tense transatlan.